TRACE ELEMENT DEGASSING AND ENRICHMENT IN THE ERUPTIVE PLUME OF THE 2000 ERUPTION OF HEKLA VOLCANO, ICELAND - Moune S.; Gauthier P.-J.; Sigmarsson O.; Gislason S.R. (My University, 2006)
During its last eruption in February 2000, Hekla volcano (Iceland) emitted a sub-Plinian plume that was condensed and scavenged down to the ground by heavy snowstorms, offering the unique opportunity to study the chemistry of the gaseous plume released during highly explosive eruptions. In this paper, we present results on trace element and minor volatile species (sulfates, chlorides, and fluorides) concentrations in snow samples collected shortly after the beginning of the eruption. The goal of this study is to better constrain the degassing and mobility of trace elements in gaseous emissions. Trace element volatility at Hekla is quantified by means of enrichment factors (EF) relative to Be. Well-known volatile trace elements (e.g., transition metals, heavy metals, and metalloids) are considerably enriched in the volcanic plume of Hekla. Their abundances are governed by the primary magmatic degassing of sulfate and/or halide compounds, which are gaseous at magmatic temperature. Their volatility is, however, slightly lower than in basaltic systems, most likely because of the lower magma temperature and higher magma viscosity at Hekla. More surprisingly, refractory elements (e.g., REE, Th, Ba, and Y) are also significantly enriched in the eruptive plume of Hekla where their apparent volatility is two orders of magnitude higher than in mafic systems. In addition, REE patterns normalized to the Hekla 2000 lava composition show a significant enrichment of HREE over LREE, suggesting the presence of REE fluorides in the volcanic plume. Such enrichments in the most refractory elements and REE fractionation are difficult to reconcile with primary degassing processes, since REE fluorides are not gaseous at magma temperature. REE enrichments at Hekla could be attributed to incongruent dissolution of tephra grains at low temperature by F-rich volcanic gases and aerosols within the eruptive plume. This view is supported by both leaching experiments performed on Hekla tephra and thermodynamic considerations on REE mobility in hydrothermal fluids and modeling of glass dissolution in F-rich aqueous solutions. Tephra dissolution may also explain the observed enrichments in other refractory elements (e.g., Th, Y, and Ba) and could contribute to the degassing mass balance of some volatile trace elements, provided they are mobile in F-rich fluids. It thus appears that both primary magmatic degassing and secondary tephra dissolution processes govern the chemistry of eruptive plumes released during explosive eruptions. © 2005 Elsevier Inc. All rights reserved.